Peptide/receptor-like kinase-mediated signaling involved in male–female interactions. (October 2019) - Zhong, Sheng; Qu, Li-Jia
Highlights: In angiosperms, successful double fertilization requires extensive male–female interactions between pollen tubes and female tissues. Peptides, mainly cysteine-rich peptides (CRPs) secreted from male or female tissues, serve as signal ligands in male–female interactions. Receptor-like kinases, paired with corresponding peptide signals, trigger different cytoplasmic responses during male–female interactions. Abstract : In flowering plants, extensive male–female interactions during pollen germination on the stigma, pollen tube growth and guidance in the transmitting tract, and pollen tube reception by the female gametophyte are required for successful double fertilization in which various signaling cascades are involved. Peptide/receptor-like kinase-mediated signaling has been found playing important roles in these male–female interactions. Here, we mainly summarized the progress made on the regulatory roles of peptide/receptor-like kinase-mediated signaling pathways in four critical stages during reproduction in higher plants.